2010
DOI: 10.1111/j.1528-1167.2009.02495.x
|View full text |Cite
|
Sign up to set email alerts
|

Interictal cerebral blood flow abnormality in cryptogenic West syndrome

Abstract: SUMMARYPurpose: To elucidate the abnormality of interictal regional cerebral blood flow (rCBF) of West syndrome at the onset. Methods: Quantitative measurement of rCBF with an autoradiography method using N-isopropyl-( 123 I) p-iodoamphetamine single photon emission computed tomography (SPECT) was performed on 14 infants with cryptogenic West syndrome. Regions of interest (ROIs) for rCBF were placed automatically using an automated ROI analysis software (three-dimensional stereotactic ROI template), and were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We emphasize the value of the latter hypothesis because previous studies supported this concept. For example, a clinical study using single photon emission tomography revealed decreased regional cerebral blood flow in the hippocampus of IS patients 39 . In rodents, ACTH was shown to regulate the hippocampal expressions of Crh and Crhbp 40 .…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize the value of the latter hypothesis because previous studies supported this concept. For example, a clinical study using single photon emission tomography revealed decreased regional cerebral blood flow in the hippocampus of IS patients 39 . In rodents, ACTH was shown to regulate the hippocampal expressions of Crh and Crhbp 40 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of interictal SPECT showed decreased perfusion of the thalamus and hippocampus in children with WS. 21 The present EEG-fMRI study suggests that epileptogenic activities during hypsarrhythmia are associated with abnormal activities in the hippocampus and thalamus and lead to dysfunction of the limbic system. This hypothesis supports the idea that early cessation of the hypsarrhythmia is important for cognitive outcomes in WS.…”
Section: Discussionmentioning
confidence: 67%